Psychoanalytic and Phenomenological Reflections on Masculinity - Karlsson, Gunnar (Taylor & Francis, 2023)
In this highly original volume, Gunnar Karlsson offers new answers to the question concerning the relationship between belonging to a specific sex as a male and striving for a masculine identity. This book offers a uniquely psychoanalytic and phenomenological perspective on masculinity. Karlsson considers masculinity and traditional masculine ideals through a psychoanalytic lens before taking phenomenological concepts to chisel out the relationship between sex and gender. This perspective is developed throughout the volume to inspire readers to further their understanding of traditional gender assignment - female, male and intersex - in light of gendered characteristics such as femininity and masculinity. Chapters span topics such as the characteristics of typical, so-called "phallic masculinity", its allure and psychogenetic explanation, as well as looking at what phallic masculinity disregards. Throughout, Karlsson maintains that phallic masculinity is unattainable, as it seeks to escape the existential conditions of helplessness, vulnerability, and dependence. He makes the case for the importance of considering the notion of ego-identity in the field of sex/gender studies, encouraging a liberation from gender stereotypes. Psychoanalytic and Phenomenological Reflections on Masculinity will be of great interest to researchers, clinical psychoanalysts and psychotherapists, as well as anyone interested in masculinity, gender studies and the relationship between sex and gender. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.